Numerical study optimation design of CPU cooling system analysis using CFD method - Yudanto, Fajar Dwi; Inderanata, Rochmad Novian; Johan, Arif Bintoro; Setuju, Setuju (Applied Engineering and Technology, 2023)
Computers often experience damage to the CPU, especially the mainboard and processor, due to several factors, including human error or excessive use and environmental conditions. Component placement is frequently utilized to improve the CPU room conditions to keep it cool. This research numerically investigates desktop PC processors and heatsink configurations for mechanical engineering vocational learning. The kind of metal material, number of fans, and fan arrangement were all tested at three levels. The computer components in this research are the CPU, heatsink, fan, and processor—a 65-watt Thermal Design Power (TDP) CPU with a constant air intake speed of 5 m/s. The criteria investigated include metal type (steel, aluminum, and copper), cooling design (horizontal, vertical, and mixed), and fan count (2-4-8). The methods used in this research are the Computational Fluid Dynamics (CFD) method and the Taguchi method to examine fluid flow characteristics and temperature. Numerical results show the maximum temperature is 123 °C in the vertical, eight-fan, and steel configurations. Minimum temperature 39.22 °C in mixed configuration, eight fans, and copper. These findings reveal that the kind of metal material, number of fans, and fan arrangement all impact the CPU cooler and heatsink configuration. However, the Taguchi method can provide a more detailed understanding of configuration.